Relationship Between Change and Development in Environmental Engineering Education in Libya - Yousaf Hassin, Dabouba; Azeezah Jumma, Abdulsamia; Mahmoud M., Dboba; W., Astiata; Satya, Bindra (INTI International University, 2023)
This study is designed to present an overview of the state of the art on new capacity-building approaches and methodologies to meet the demands of sustainable development at global, regional, national, and local levels. A brief description of current barriers to integrating sustainability into engineering education demonstrates how New Libya is playing a vital role in effective education and training in environmental engineering using the teaching and learning practices employed in green engineering courses and the best practice UNIDO PRIME & GRIP, UNESCO MAB and MOST blended learning approach that helps level the varied content knowledge, expertise, and experience of professionals. It highlights a strategy and plan of action to meet the challenges of change and development in education and training required to develop the vital skills and experience of sustainable development professionals needed to perform their more sophisticated jobs with greater coordination and prioritization among aviation stakeholders. Finally, it provides a framework approach using outcomes, output, baseline, targets, performance indicators, and activities to design a wide range of formal education and training in environmental protection fields using new blended learning technologies for the enhancement of sustainable livelihoods in general and Libya in particular.